A Gypsy Future - Tanabe, James (Sens public)

(untitled) (Département des littératures de langue française, 2010)
A title, even “Artistic Director for Cirque du Soleil”, barely summarizes all the dimensions of James Tanabe. A graduate of the Massachusetts Institute of Technology (MIT) where he triple-majored in Planetary Science, Physics, and Biology, he seemed destined to continue his work at NASA or at the prestigious Mayo Clinic. However, he drops everything to join the National Circus School of Montreal in 2001 and graduates in 2004. After performing in several shows around the world, he co-founds New Circus Asia in 2007, which produces its own shows in almost every country between Istanbul and Tokyo. Cirque du Soleil spots him and hires him as an Artistic Director in 2009, the youngest one ever hired to that position. A polyglot, he pursues his wandering all around the world and those who were privileged enough to read his writings about his voyages know he is also among the most gifted writers of his generation. At the request of Sens Public, he shared a few thoughts about the future of circus.